2021
DOI: 10.3389/fped.2021.641318
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram Predicting the Prognosis of Children With Biliary Atresia After Hepatoportoenterostomy

Abstract: Background: Although Kasai portoenterostomy (KPE) is performed timely for most children with biliary atresia (BA), the native liver survival (NLS) is still poor due to the progressive liver fibrosis. Many children have to receive liver transplantation (LT) within 2 years after KPE. Early prediction of the prognosis permits the implementation of prophylactic treatments for BA children. However, studies about the prediction are limited.Objective: The purpose of this study is to establish a nomogram to predict th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
7
2
Order By: Relevance
“…Wu et al found that an LSM value > 7.7 kPa was a predictive factor for discriminating BA patients from other cholestatic patients, and patients with an LSM value > 16 kPa often require early liver transplantation ( 29 ). Liu et al also showed that the LSM value at 3 months was associated with 2-years NLS post- KP ( 31 ). In our study, the preoperative LSM values in the uncleared jaundice group were significantly higher.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Wu et al found that an LSM value > 7.7 kPa was a predictive factor for discriminating BA patients from other cholestatic patients, and patients with an LSM value > 16 kPa often require early liver transplantation ( 29 ). Liu et al also showed that the LSM value at 3 months was associated with 2-years NLS post- KP ( 31 ). In our study, the preoperative LSM values in the uncleared jaundice group were significantly higher.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the LSM value mainly reflects the degree of liver fibrosis, which is one of the main pathological features of BA (28). Previous studies have applied the LSM assessment for the diagnostic and prognostic prediction of BA (29)(30)(31). Wu et al found that an LSM value > 7.7 kPa was a predictive factor for discriminating BA patients from other cholestatic patients, and patients with an LSM value > 16 kPa often require early liver transplantation (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DB and ALB are factors reflecting the excretory and synthetic functions of liver; the results indicate that only patients with excellent comprehensive liver functions can survive with their native liver. Some studies have been reported about predicting NLS for infants after KPE, most focused on factors before jaundice resolution, and some are not routine parameters, [9][10][11][12][13][14][15] the predictive values are not certain.…”
Section: Kpe Remains the First Surgical Choice For Biliary Atresia Co...mentioning
confidence: 99%
“…Many studies have tried to identify the outcome predictors after KPE. Several studies (26)(27)(28)(29)(30) reported that pre-KPE liver biopsy and elastography can predict KPE outcome by evaluating liver degree. However, although liver biopsy is the gold standard for fibrosis, it is invasive and unsafe for BA infants, and the obtained histological material is insufficient for an appropriate analysis (27).…”
Section: Introductionmentioning
confidence: 99%